Heroin‐induced respiratory depression and the influence of dose variation: within‐subject between‐session changes following dose reduction - Tas, Basak; Jolley, Caroline J.; Kalk, Nicola J.; Waal, Rob; Bell, James; Strang, John (Addiction (Abingdon, England), 2020)
Background and aims Globally, more than 100 000 people die annually from opioid overdose. Opportunities to study physiological events in at‐risk individuals are limited. This study examined variation of opioid dose and impact on respiratory depression in a chronic injecting heroin user at separate time‐points during his long‐term diamorphine maintenance treatment. Design A single‐subject study over 5 years during which participant underwent experimental studies on diamorphine‐induced respiratory depression, at changing maintenance doses. Setting A clinical research facility. Participant Male subject on long‐term injectable diamorphine (pharmaceutical heroin) maintenance treatment for heroin addiction. Measurements Physiological measures of oxygen saturation (SpO2), end‐tidal carbon dioxide (ETCO2) and respiratory rate (RR) were used to indicate severity of respiratory depression. Findings (1) After diamorphine injection, respiratory regulation became abnormal, with prolonged apnoea exceeding 20 sec (maximum 56 sec), elevated ETCO2 (maximum 6.9%) and hypoxaemia (minimum SpO2 80%). (2) Abnormalities were greater with highest diamorphine dose: average SpO2 was 89.3% after 100 mg diamorphine versus 93.6% and 92.8% for the two 30‐mg doses. (3) However, long apnoeic pauses and high levels of ETCO2% were also present after lower doses. Conclusions With marked inter‐session variability, these findings corroborate observations of inconsistent relationships between opioid dose and overdose risk.